Adult cardiac transplantation utilizing donors after circulatory death - Rajah, Tanisha; Blitzer, David; Silvestry, Scott; Copeland, Hannah (Annals of Cardiothoracic Surgery; Vol 13, No 6 (November 30, 2024): Heart Transplantation In Controlled Donation After Circulatory Death I, 2024)
Donation after circulatory death (DCD) presents both opportunities and challenges in the realm of heart transplantation. Its emergence holds promise for narrowing the gap between patients in need of organs and the available donor pool. The rapid emergence of DCD use has allowed heart transplant volume to increase worldwide. Long-term outcomes and best practices remain to be defined and are important considerations in the wider use of these techniques in a broad selection of patients to understand best use and practice moving forward. Expanding DCD donation entails substantial resource allocation, coordination efforts, and training initiatives. Moving forward, standardization is imperative, particularly in aspects such as “stand-off” time, warm ischemic time (WIT), and perfusate composition.